Study of mesoporous CdS-quantum-dot-sensitized TiO2 films by using X-ray photoelectron spectroscopy and AFM - Ghazzal, Mohamed Nawfal; Wojcieszak, Robert; Raj, Gijo; Gaigneaux, Eric M (Beilstein journal of nanotechnology, 2014)
CdS quantum dots were grown on mesoporous TiO 2 films by successive ionic layer adsorption and reaction processes in order to obtain CdS particles of various sizes. AFM analysis shows that the growth of the CdS particles is a two-step process. The first step is the formation of new crystallites at each deposition cycle. In the next step the pre-deposited crystallites grow to form larger aggregates. Special attention is paid to the estimation of the CdS particle size by X-ray photoelectron spectroscopy (XPS). Among the classical methods of characterization the XPS model is described in detail. In order to make an attempt to validate the XPS model, the results are compared to those obtained from AFM analysis and to the evolution of the band gap energy of the CdS nanoparticles as obtained by UV–vis spectroscopy. The results showed that XPS technique is a powerful tool in the estimation of the CdS particle size. In conjunction with these results, a very good correlation has been found between the number of deposition cycles and the particle size.